Association Between ABO Blood Group System and COVID-19 Susceptibility in Wuhan - Fan, Qian; Zhang, Wei; Li, Bo; Li, De-Jia; Zhang, Jian; Zhao, Fang (Frontiers in Cellular and Infection Microbiology, 2020)
Background: The ABO blood group system has been associated with multiple infectious diseases, including hepatitis B, dengue haemorrhagic fever and so on. Coronavirus disease 2019 (COVID-19) is a new respiratory infectious disease and the relationship between COVID-19 and ABO blood group system needs to be explored urgently. Methods: A hospital-based case-control study was conducted at Zhongnan Hospital of Wuhan University from 1 January 2020 to 5 March 2020. A total of 105 COVID-19 cases and 103 controls were included. The blood group frequency was tested with the chi-square statistic, and odds ratios (ORs) with 95% confidence intervals (CIs) were calculated between cases and controls. In addition, according to gender, the studied population was divided into two subgroups, and we assessed the association between cases and controls by gender. Finally, considering lymphopenia as a feature of COVID-19, the relationship between the ABO blood group and the lymphocyte count was determined in case samples. Results: The frequencies of blood types A, B, AB and O were 42.8%, 26.7%, 8.57% and 21.9%, respectively, in the case group. Association analysis between the ABO blood group and COVID-19 indicated that there was a statistically significant difference for blood type A (P=0.04, OR=1.33, 95% CI=1.02-1.73) but not for blood types B, AB or O (P=0.48, OR=0.90, 95% CI=0.66-1.23; P=0.61, OR=0.88, 95% CI=0.53-1.46; and P=0.23, OR=0.82, 95% CI=0.58-1.15, respectively). An analysis stratified by gender revealed that the association was highly significant between blood type A in the female subgroup (P=0.02, OR=1.56, 95% CI=1.08-2.27) but not in the male subgroup (P=0.51, OR=1.14, 95% CI=0.78-1.67). The average level of lymphocyte count was the lowest with blood type A in patients, however, compared with other blood types, there was still no significant statistical difference. Conclusions: Our findings provide epidemiological evidence that females with blood type A are susceptible to COVID-19. However, these research results need to be validated in future studies.